PREVENTIVE FUNCTION OF THE PENITENTIARY SYSTEM AND ISSUES OF INCREASING ITS EFFECTIVENESS (World Bulletin of Management and Law, 2023)
This article analyzes the role of penitentiary policy in achieving the goals of criminal punishment from a legal point of view. In many countries and in the modern criminal law doctrine as a whole, punishment is used to correct the morality of the convict, to prevent him from continuing his criminal activity, to restore social justice, and to prevent both the convict and other persons from committing a new crime. In the article, he analyzed the best practices of foreign countries and the approaches of legal scholars to the form of public administration in this regard.
Keywords: penitentiary system; convict; sentencing; execution of punishment